1991
DOI: 10.1073/pnas.88.7.2758
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol rapidly reduces prolactin release and cAMP and 45Ca2+ accumulation in the cichlid fish pituitary in vitro.

Abstract: During in vitro incubation, prolactin release is inhibited in a dose-related manner by cortisol. This action is mimicked by the synthetic glucocorticoid agonist dexamethasone but not by other steroids tested. Perifusion studies indicate that the inhibition of [3Hjprolactin release by cortisol occurs within 20 min. Cortisol (50 nM) also inhibits cAMP accumulation and reduces 4CaZ+ accumulation in the tilapia rostral pars distalis within 15 nmin. Cortisol's action on prolactin release is blocked in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 37 publications
(38 reference statements)
1
30
1
1
Order By: Relevance
“…Even though extensive evidence has shown that ACTH and other stress-related compounds also affect memory retrieval (Izquierdo and Pereira 1989;Borde et al 1997Borde et al , 1998Borde and Beracochea 1999;Vianna et al 2000), several arguments suggest a causal role of glucocorticoids in the stressinduced modulation of memory retrieval. First, glucocorticoids can exert their effects either by long genomic mechanisms involving glucocorticoid and mineralocorticoid receptors (Douma et al 1998) or by more rapid (between a few seconds to several minutes) nongenomic mechanisms (Borski et al 1991;Rose et al 1993;Breuner et al 1998;De Quervain et al 1998). Second, a recent study carried out by our team showed that the increase of the delay between acute stress delivery and retention testing (2 h instead of 5 min; i.e., so far, memory retrieval took place when plasmatic corticosterone got back to basal level) totally abolished the stress-induced retrieval modulation in the CSD task (A. Celerier, C. Pierard, A.…”
Section: Discussionmentioning
confidence: 99%
“…Even though extensive evidence has shown that ACTH and other stress-related compounds also affect memory retrieval (Izquierdo and Pereira 1989;Borde et al 1997Borde et al , 1998Borde and Beracochea 1999;Vianna et al 2000), several arguments suggest a causal role of glucocorticoids in the stressinduced modulation of memory retrieval. First, glucocorticoids can exert their effects either by long genomic mechanisms involving glucocorticoid and mineralocorticoid receptors (Douma et al 1998) or by more rapid (between a few seconds to several minutes) nongenomic mechanisms (Borski et al 1991;Rose et al 1993;Breuner et al 1998;De Quervain et al 1998). Second, a recent study carried out by our team showed that the increase of the delay between acute stress delivery and retention testing (2 h instead of 5 min; i.e., so far, memory retrieval took place when plasmatic corticosterone got back to basal level) totally abolished the stress-induced retrieval modulation in the CSD task (A. Celerier, C. Pierard, A.…”
Section: Discussionmentioning
confidence: 99%
“…This instance of Prl-cortisol antagonism, at play in the gill, operates in concert with the modulation of Prl cell function by cortisol. In the pituitary, cortisol inhibits Prl release within minutes via nongenomic mechanisms (Borski et al 1991). Recent advances in our understanding of how the teleost gill operates at the molecular level have provided the fodder for identifying novel, and conserved, hormone targets (Breves et al 2014a, Guh et al 2015.…”
Section: :3mentioning
confidence: 99%
“…Studies in our laboratory have shown that cortisol rapidly reduces PRL release (Ͻ20 min) through a Ca 2ϩ -dependent mechanism that involves comparably rapid reductions in 45 Ca 2ϩ accumulation (Ͻ15 min) (8). The rapid effect of cortisol is not mediated by changes in gene expression, since the protein synthesis blocker cycloheximide was unable to overcome PRL release inhibited by cortisol (10).…”
mentioning
confidence: 99%
“…In contrast with PRL, cortisol is an important seawater osmoregulatory hormone that promotes Na ϩ excretion and thereby reduces the rise in blood osmolality that occurs when animals move to hyperosmotic environments (35). Cortisol may also inhibit the secretion of PRL, whose actions counteract seawater adaptation, to promote osmoregulation in seawater (8,50).…”
mentioning
confidence: 99%
See 1 more Smart Citation